(untitled) (Baghdad Science Journal, 2020)
The development of the internet of things (IoT) and the internet of robotics (IoR) are becoming more and more involved with our daily lives. It serves a variety of tasks some of them are essential to us. The main objective of SRR is to develop a surveillance system for detecting suspicious and targeted places for users without any loss of human life. This paper shows the design and implementation of a robotic surveillance platform for real-time monitoring with the help of image processing, which can explorer places of difficult access or high risk. The robotic live streaming is via two cameras, the first one is fixed straight on the road and the second one is dynamic with tilt-pan ability. All cameras have image processing capabilities to analyze, detect and track objects plus few other graphical functions. The components mentioned above built on top of the four-wheel vehicle system with high torque to provide mobility on rough terrain. This work is based on Raspberry Pi and can be controlled over Wi-Fi locally or publicly over the internet. The results show making a high potential, relatively low price robot with lots of features and functions that can perform multiple tasks simultaneously, all are crucial to surveillance and monitoring problems, controlled by a user from far distances and for a long time.